2016–2017 Central Italy Earthquake Sequence: Seismic Retrofit Policy and Effectiveness. Issue 4 (November 2018) - Mazzoni, Silvia; Castori, Giulio; Galasso, Carmine; Calvi, Paolo; Dreyer, Richard; Fischer, Erica; Fulco, Alessandro; Sorrentino, Luigi; Wilson, Jay; Penna, Andrea; Magenes, Guido
The 2016–2017 Central Italy earthquake sequence consisted of several moderately high-magnitude earthquakes, between M5.5 and M6.5, each centered in a different location and with its own sequences of aftershocks spanning several months. To study the effects of this earthquake sequence on the built environment and the impact on the communities, a collaborative reconnaissance effort was organized by the Earthquake Engineering Research Institute (EERI), the Eucentre Foundation, the European Centre for Training and Research in Earthquake Engineering (EUCentre), and the Rete dei Laboratori Universitari di Ingegneria Sismica (ReLuis). The effort consisted of two reconnaissance missions: one following the Amatrice Earthquake of 24 August 2016 and one after the end of the earthquake sequence, in May 2017. One objective of the reconnaissance effort was to evaluate existing strengthening methodologies and assess their effectiveness in mitigating the damaging effects of ground shaking. Parallel studies by the Geotechnical Extreme Events Reconnaissance (GEER) Association, presented in a companion paper, demonstrate that variations in-ground motions due to topographic site effects had a significant impact on damage distribution in the affected area. This paper presents that, in addition to these ground motion variations, variations in the vulnerability of residential and critical facilities were observed to have a significant impact on the level of damage in the region. The damage to the historical centers of Amatrice and Norcia will be used in this evaluation: the historical center of Amatrice was devastated by the sequence of earthquakes; the significant damage in Norcia was localized to individual buildings. Amatrice has not experienced the same number of devastating earthquakes as Norcia in the last 150 years. As a result, its building stock is much older than that of Norcia and there appeared to be little visual evidence of strengthening of the buildings. The distribution of damage observed throughout the region was found to be indicative of the effectiveness of strengthening and of the need for a comprehensive implementation of retrofit policies.